Tourism Attractions and Visitors Perceptions on “Negeri di Atas Awan”, A New Tourist Destination in Citorek Kidul Lebak Banten - Nofiyanti, Fifi; Mayasari, Ira; Parwoto, Boby Dimas (Institut Pariwisata Trisakti, 2020)
This study aims to determine the tourist attraction and perceptions of visitors on the new tourists’ destination called Negeri di atas Awan (the country above the clouds) located in Citorek Kidul Village, Lebak Banten, Indonesia. This tourist destination was viral in September 2019 was briefly used by several citizens, because Lebak Banten has never been heard of having a tourist destination. The area is 900 meters above sea level. This research method is qualitative with a case study approach. By using this type of case study research, this study intends to provide a description of the Tourism Attraction and Perceptions in Citorek Kidul Lebak Village, Banten, which is being viral on social media. The study was conducted in the Citorek Kidul Lebak Village, Banten, which is known for its country tourism on clouds. The results of this study are the tourist attraction of